2016
DOI: 10.1007/s12206-016-0506-x
|View full text |Cite
|
Sign up to set email alerts
|

Vibration analysis of orthotropic circular and elliptical nano-plates embedded in elastic medium based on nonlocal Mindlin plate theory and using Galerkin method

Abstract: In the present study a continuum model based on the nonlocal elasticity theory is developed for free vibration analysis of embedded orthotropic thick circular and elliptical nano-plates rested on an elastic foundation. The elastic foundation is considered to behave like a Pasternak type of foundations. Governing equations for vibrating nano-plate are derived according to the Mindlin plate theory in which the effects of shear deformations of nano-plate are also included. The Galerkin method is then employed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Inserting Equations ( 23) and (24) into Equation ( 22), integrate the spatial coordinate variables by parts, and classify the coefficients of 𝛿𝜓 and đ›żđ‘€ to obtain the two motion governing differential equations of the graded porous circular nanoplate as follows…”
Section: Governing Equation Of Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inserting Equations ( 23) and (24) into Equation ( 22), integrate the spatial coordinate variables by parts, and classify the coefficients of 𝛿𝜓 and đ›żđ‘€ to obtain the two motion governing differential equations of the graded porous circular nanoplate as follows…”
Section: Governing Equation Of Motionmentioning
confidence: 99%
“…The results show that if the nonlocal effect is ignored for nanoplates, there is a large error in the research results. On the bases of ENET, Anjomshoa and Tahani [24] studied the free vibration of Orthotropic thick circular nanoplates on elastic foundation, and applied this method to the free vibration analysis of elliptical nanoplates. Studies had shown that compared with the classical theory, the nonlocal frequency of nanoplates is smaller, which is more obvious in smaller length and higher vibration mode.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Anjomshoa 9 investigated the application of Ritz functions in the buckling analysis of micro-or nano-elliptical and circular orthotropic plates, based on both nonlocal elasticity theory and the Galerkin method. 10 These authors found that the critical buckling load is highly dependent on the non-localization of micro-or nano-elliptical plates, especially as it relates to the microscopic dimensions. In the same context, Anjomshoa et al 11 presented the frequency analysis of micro-or nano-orthotropic circular and elliptical plates, using the principle of nonlocal variation based on the nonlocal classical plates theory (NCPT).…”
Section: Literature Reviewmentioning
confidence: 99%